Discerning trends in international metal prices in the presence of non-stationary volatility - Tony Addison; Atanu Ghoshray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Modelling the underlying long-run trend of metal prices is important, given that selected metals are a source of income for many countries. However, estimating the underlying trend has proven to be difficult, given the persistence and volatility of primary commodity prices-metals are no exception. Recent events have led experts to believe that trends have been undergoing large swings; whether these movements are temporary or contribute to the trend being characterized by broken piecewise trends over certain lengths of time remains a contentious issue. We combine robust econometric procedures to calculate the trend, which could be secular or broken, for selected metal prices over a century. We find support for the conjecture that, based on the unpredictable shifts in demand, extraction costs, and discovery of reserves, it is highly possible to expect that prices may be subject to large variability that overshadows any underlying trend.
Keywords: C22; Q02; Q32; 330; trends; metal prices; volatility; persistence